The Study of Education for Ethnic-racial Relations in Undergraduate Courses at UFBA - Renata Veras (2021)
Teacher education in a decolonial perspective requires reflecting on subjects subordinated by coloniality to hegemonic and Eurocentric educational logics. In this sense, the question arises: how has education for ethnic-racial relations been included in the curriculum of undergraduate courses at the Federal University of Bahia? The aim of this study is to analyze the inclusion of education for ethnic-racial relations in the curricula of undergraduate courses at the Federal University of Bahia. Therefore, it was identified that of the 1004 components offered in the mandatory matrix of these courses, 27 contained themes focused on the racial issue. This is a cross-sectional, exploratory, qualitative study. Data were analyzed using descending hierarchical classification and similarity trees with the support of the IRAMUTEQ software. The History course was the one that most offered components of this nature, while those in Biological Sciences, Computing, Mathematics and Chemistry were the ones with the lowest offer. The analysis of the descending hierarchical classification and similarity revealed that the most frequent themes were related to the history of Brazil, including education and culture. The importance of mainstreaming in the teacher education themes such as: ethnic-racial diversity in Brazil, its socio-political, economic, cultural, educational and artistic contributions, as well as critical reflection on racial discrimination and oppression is emphasized. The initiative to explore the topic in a decolonial and transgressive perspective has the potential to generate changes in citizen education since early childhood education, in favor of a more just and less unequal society.